Estudo teórico de nanotubos de nitreto de boro com dopagens do tipo n e suas interações com gases neurotóxicos - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
In this work we studied the models of single walled boron nitrate (BN) nanotubes. The templates were obtained from hexagonal plane enrollment using algorithms made in bash shell programming language. From the coordinates of the atoms, they were made as optimizers of bonding distances, bonding angle and torsion angles using the PM7 semi-economical method. Evidence is tailored to lower interest rates. In order for the issues to be eliminated, hydrogenated as model ends, to be returned in an exaggerated manner and can be caused by the free valence ends. The optimized coordinates were collected and placed in B3LYP Functional Density Theory (DFT) calculations with the 6-311G and 6-311G (d, p) base set. The difference | HOMO - LUMO | It was calculated to be a nature of electrical conductivity of the material and can be seen at the same formation angle with the chirality of the material or with the diameter, making the nanotubes formed by sludge nitride are promising for a material production. The dipolar moment was also analyzed and it was observed that the structures with symmetry (armchair) have a tendency to be nonpolar, while the asymmetry (zigzag) causes a polarization in the structure. In order to improve the electronic properties of the material in gas adsorption, such as the energy gap, it produced a generation of non-material defects by replacing boron with atoms as part of group 14 in the solid structures. It's called n-type doping. It was observed that as the van de Waals level of the doping atom increases the gap variation tends to leave the gap structures larger than the previous ones. The doping of the indexing model to its electronic variables was also observed with the emergence of nucleophilic and ceramic regions. After doping, its effect on the adsorption of neurotoxic gases was observed, and it was observed that the atom-doped models are promising candidates for the detection of neurotoxic gases, such as sarin gas and soman gas, having an average formation energy of 13.10 kcal / mol and an average energy gap of 4.60 eV.
Theoretical study of n-doped boron nitride nanotubes and their interactions with neurotoxic gases
Keywords: Nanotubos; Nitreto de Boro; Sensores; Agentes neurotóxicos; Nanotubes; Boron nitride; Sensors; Neurotoxic Agents; CIENCIAS EXATAS E DA TERRA::QUIMICA